Board Directors and Corporate Social Responsibility - Mariana Nedelcu (Bunea) (Amfiteatru Economic)
The boards of directors and corporate social responsibility (CSR) have been the subject of much study and debate in the corporate governance circles over the two last decades. With issues ranging from poor corporate reporting to excessive executive compensation often splashed in the headlines, the role of boards comes into the media limelight as never before. Boards of directors are also becoming increasingly aware of corporate social responsibility issues.